2016
DOI: 10.1136/bmjopen-2016-012721
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities for earlier diagnosis of HIV in patients who presented with advanced HIV disease: a retrospective cohort study

Abstract: ObjectiveTo quantify and characterise missed opportunities for earlier HIV diagnosis in patients diagnosed with advanced HIV.DesignA retrospective observational cohort study.SettingA central tertiary medical centre in Israel.MeasuresThe proportion of patients with advanced HIV, the proportion of missed opportunities to diagnose them earlier, and the rate of clinical indicator diseases (CIDs) in those patients.ResultsBetween 2010 and 2015, 356 patients were diagnosed with HIV, 118 (33.4%) were diagnosed late, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 28 publications
3
34
1
1
Order By: Relevance
“…Routine testing for HIV in the presence of IC has been demonstrated to be cost effective . Failure to screen for HIV when patients intersect with the healthcare system with an IC represents a missed opportunity for earlier diagnosis . Other studies have demonstrated that among patients presenting with IC, rates of HIV testing are low .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Routine testing for HIV in the presence of IC has been demonstrated to be cost effective . Failure to screen for HIV when patients intersect with the healthcare system with an IC represents a missed opportunity for earlier diagnosis . Other studies have demonstrated that among patients presenting with IC, rates of HIV testing are low .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated that among patients presenting with IC, rates of HIV testing are low . Multiple barriers to testing have been identified including lack of knowledge of IC, lack of guidelines, low‐risk perception and perceived lack of knowledge around HIV . Studies reviewing non‐HIV specialty guidelines for IC found that many of these guidelines do not consider HIV testing as part of the investigations for IC .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This figure compares to 53% mentioning and 38% recommending HIV testing in comparable UK findings. 16 In our own experience 15 and the experience of others, [19][20][21][22] missed opportunities for diagnosis are likely to be followed by later presentation to hospital with AIDS-defining events. Early diagnosis and screening are likely to reduce morbidity and mortality and be cost effective.…”
Section: Discussionmentioning
confidence: 92%